Fabrication of NiO/RGO nanocomposite for enhancing photocatalytic performance through degradation of RhB. (May 2023) - Vivek, P.; Sivakumar, R.; Selva Esakki, E.; Deivanayaki, S.
Abstract: In this study, NiO/RGO nanocomposites have been synthesized by a facile hydrothermal method. The chemical structure of nanocomposites was validated through X-Ray diffraction (XRD), Raman spectra, and X-Ray photoelectron spectroscopy analysis. Field Emission Scanning Electron spectroscopy (FESEM) and High-Resolution Transmission Microscopy (HRTEM) were used to investigate the morphological investigations. The bandgap of NiO was reduced after incorporation with RGO, revealed by UV-DRS spectroscopy. The NiO/RGO nanocomposites show better photocatalytic performance for degrading RhB dye. The NiO/RGO nanocomposites display the highest rate constant of 0.015871 min −1, which is 1.4 times higher than NiO. The Scavenging test confirmed that OH radicals are involved in the photodegradation process. The cyclic test validated the photocatalyst's stability. This NiO/RGO nanocomposite has proven to be an excellent catalyst for eliminating organic pollutants from wastewater. Highlights: A novel NiO/RGO nanocomposite synthesized by a hydrothermal method. The NiO/RGO nanocomposite exhibited higher photocatalytic activity than pristine NiO under UV light irradiation. The photocatalytic degradation efficiency of the fabricated nanocomposites showed a high potential for RhB dye degradation (95.4%) Compared to pure NiO (86%) under UV light irradiation. The scavenger test suggested that OH radicals participated in the RhB dye degradation process. Predominantly, NiO/RGO nanocomposite could be an effective photocatalyst for removing various organic pollutants from wastewater.